A non-PCR SPR platform using RNase H to detect MicroRNA 29a-3p from throat swabs of human subjects with influenza A virus H1N1 infection - Loo, Jacky; Wang, S. S.; Peng, F.; He, J. A.; He, L.; Guo, Y. C.; Gu, D. Y.; Kwok, H. C.; Wu, S. Y.; Ho, H. P.; Xie, W. D.; Shao, Y. H.; et al. (Analyst (London), 2015)
As in all RNA viruses, influenza viruses change and mutate constantly because their RNA polymerase has no proofreading ability. This poses a serious threat to public health nowadays. In addition, traditional pathogen-based detection methods may not be able to report an infection from an unknown type or a subtype of virus if its nucleotide sequence is not known. Because of these factors, targeting host microRNA signatures may be an alternative to classify infections and distinguish types of pathogens as microRNAs are produced in humans shortly after infection. Although this approach is in its infant stage, there is an urgent need to develop a rapid reporter assay for microRNA for disease control and prevention. As a proof of concept, we report herein for the first time a non-PCR MARS (MicroRNA-RNase-SPR) assay to detect the microRNA miR-29a-3p from human subjects infected with influenza virus H1N1 by surface plasmon resonance (SPR). In our MARS assay, RNase H is employed to specifically hydrolyze the RNA probes immobilized on the gold surface where they hybridize with its cognate target cDNAs miR-29a-3p, where it was formed from reverse transcription with mature miR-29a-3p specific stem-looped primers. After the digestion of the RNA probe by RNase H, the intact cDNA was released from the RNA–DNA hybrid and bound to a new RNA probe for another enzymatic reaction cycle to amplify signals. With assay optimization, the detection limit of our MARS assay for miR-29a-3p was found to be 1 nM, and this new assay could be completed within 1 hour without thermal cycling. This non-PCR assay with high selectivity for mature microRNA provides a new platform for rapid disease diagnosis, quarantine and disease control.